Blood donation for iron removal in individuals with HFE mutations: study of efficacy and safety and short review on hemochromatosis and blood donation - Infanti, Laura; Leitner, Gerda; Moe, Morten; Pehlic, Vildana; Cattaneo, Marco; Benkert, Pascal; Holbro, Andreas; Passweg, Jakob; Worel, Nina; Buser, Andreas (Frontiers in Medicine, 2024)
We present the results of a study of iron removal in preclinical hemochromatosis (HC) and in asymptomatic individuals with other HFE genotypes as performed in the highly regulated setting of blood donation. The scope of the study was to analyze the impact of frequent treatment procedures on healthy persons discovered to carry HFE variants and having elevated ferritin. Such individuals are frequently referred to blood donation centers, although the indication for treatment does not always comply with current published guidelines. An intensive iron removal treatment results in potentially harmful side effects also in otherwise healthy individuals. This aspect must be considered in the clinical management of persons with preclinical HC or with other conditions where iron removal is indicated. Our data point out that unnecessary iron removal in asymptomatic individuals should be avoided and that, when indicated, a less aggressive treatment should be the choice in subjects with moderately elevated ferritin and no symptoms of iron overload. A further aim of the present article is to provide clinicians with information on the advantages and limits of blood donation as a therapeutic option, and to illustrate the complexity of the issue of offering this service in a blood donation facility.